Technological Readiness of Indonesia's Photovoltaic Sector: A Technometric Analysis - Atikah, Nurul; Ashari Syawal, Ferdy (Talenta Publisher, 2025)
Despite Indonesia's vast solar potential (207.8 GWp), its utilization remains far below the 2025 target (0.87 GW), hampered by unmapped industrial capabilities. This study addresses this gap by mapping the technological capabilities of Indonesia's photovoltaic (PV) industry and its supporting sectors using Technometric models. By adopting a quantitative survey methodology involving key industry players (n=3) representing the solar panel, cable, and mounting structure sectors , the study evaluated technoware (T), humanware (H), and infoware (I) components. The main results show that the solar panel industry has “excellent” technology content with a Technology Contribution Coefficient (TCC) of 0.7204 , driven by strong humanware and infoware contributions (both exceeding 70%). In contrast, cable companies, with a TCC of 0.5651 , are categorized as having “good” technology content, indicating a need to improve technoware, which only contributes 47%. Meanwhile, the structure (mounting) company also showed “very good” technological capability with a TCC of 0.7297. The TCC value, which ranges from 0 to 1, measures the contribution of technology in value-added creation, with values of 0.7-0.9 indicating an “excellent” category. The proposed recommendations include prioritizing technoware development through product design computing and test optimization, humanware improvement through innovation training, and infoware strengthening through comprehensive information dissemination. This study provides the first Technometric benchmark for the Indonesian PV sector, offering a clear diagnostic tool for policymakers and industry to enhance competitiveness and achieve sustainable growth targets.